Crustal deformation of the Central Indian Ocean, south of Sri Lanka as inferred from gravity and magnetic data - Kumar, Sistla Ravi (Wydawnictwa AGH, 2022)
Bathymetry, gravity, and magnetic data across the Central Indian Ocean Basin (CIOB) along a WE track between 5°N to 1°N latitudes and 77°E to 90°E longitudes are used to identify crustal deformation due to tectonic features such as the Comorin Ridge, 85°E ridge, Ninety East Ridge, and major fracture zones. The tectonic features were interpreted along the North Central Indian Ocean using 2D gravity modelling to understand the origin and tectonic activity of the subsurface features. The Comorin Ridge is coupled with gravity anomalies with small amplitude varying 25-30 mGal in comparison with the ridge relief which suggests that the ridge is compensated at deeper depths. The focus of the present study is to prepare a reasonable crustal model of the Central Indian Ocean using gravity and magnetic data. The crustal depths of the Central Indian Ocean Basin (CIOB) determined from gravity data using the spectral method are compared with the 2D gravity modelling results. It has been observed that the crustal depths obtained from the Spectral method are in good correlation with results obtained from 2D gravity modelling. The average basement depths for the profiles were obtained as ~5 km and perhaps deviated approximately 1-2 km from the mean. In the case of curie isotherm, the crustal depths vary 9-12 km for all magnetic profiles which may indicate deformation.
Geology, Geophysics & Environment
Keywords: CIOB; deformation; tentative; basement; tectonic; 2D gravity model